ENHANCING LISTENING SKILL OF THE SECOND SEMESTER STUDENTS OF ENGLISH TADRIS STUDY PROGRAM OF UIN DATOKARAMA PALU THROUGH LISTENING MONOLOGUE TEXTS - Afifah, Afifah; Wahyuni, Sri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research focuses on answering the research question “Can the use of listening monologue texts enhance listening skill of the second semester students of English Tadris Study Program of UIN Datokarama Palu?” The sample of this research is thirty second semester students of English Tadris Study Program of UIN Datokarama Palu. The researchers applied pre-experimental research design to answer the research question. By using total sampling technique, the researchers conducted a test to all of the samples. Pre-test was conducted before the treatment, while post-test was administered after the treatment. Both tests were in the form of fill-in-the blank. The treatment was handled by the researchers for five meetings. Based on the hypothesis testing, the researchers found that the value of t-test is 18.699, which is higher than the value of t-table (2.04) by using 0.05 level of significance and 29 degree of freedom. As a result, the alternative hypothesis is accepted. In other words, the use of listening monologue texts can enhance listening skill of the second semester students of English Tadris Study Program of UIN Datokarama Palu.